2010
DOI: 10.1111/j.1365-2745.2010.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenological changes in six Australian subalpine plants in response to experimental warming and year‐to‐year variation

Abstract: Summary 1.The likely phenological responses of plants to climate warming can be measured through experimental manipulation of field sites, but results are rarely validated against year-to-year changes in climate. Here, we describe the response of 1-5 years of experimental warming on phenology (budding, flowering and seed maturation) of six common subalpine plant species in the Australian Alps using the International Tundra Experiment (ITEX) protocol. 2. Phenological changes in some species (particularly the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
6
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 32 publications
2
52
6
3
Order By: Relevance
“…Nevertheless, other studies that only altered growing season temperatures found that the same species as in our study showed phenological advances under air warming [18] or that other alpine species showed a lagged response after multiple years of warming [10]. The distinct methodologies applied in these experiments (e.g.…”
Section: Discussionmentioning
confidence: 51%
“…Nevertheless, other studies that only altered growing season temperatures found that the same species as in our study showed phenological advances under air warming [18] or that other alpine species showed a lagged response after multiple years of warming [10]. The distinct methodologies applied in these experiments (e.g.…”
Section: Discussionmentioning
confidence: 51%
“…Artificial warming has frequently been reported to either advance or delay the time of flowering (Sherry et al. , 2007; Hoffmann et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, data from experimental warming studies indicate that many species that initiate leaf growth and flowering earlier also reach seed maturation and senesce earlier, shortening their active and reproductive periods [6][7][8][9][10] . A conceptual model to explain this apparent contradiction 11 , and an analysis of the effect of elevated CO 2 -which can delay annual life cycle events 12-14 -on changing season length, have not been tested.…”
mentioning
confidence: 99%